The factors shaping entrepreneurial intentions - Bagheri, Afsaneh; Lope Pihie, Zaidatol Akmaliah (Cambridge Scholars Publishing, 2014)
This book is a combination of chapters exploring the entrepreneurial attributes of university students and specifically their intentions to become entrepreneurs. It provides detailed insights into the personal and environmental factors that affect university students’ decisions to establish their own businesses. The first six chapters explore these factors through an exploratory approach and provide descriptive data on students’ entrepreneurial attributes such as self-regulation, self-efficacy, skills, metacognition (knowledge of cognition and regulation of cognition) and subjective and social norms of entrepreneurship. In these chapters, the authors provide an overall picture of entrepreneurial attributes among students from both public and private universities. The last three chapters examine students’ entrepreneurial intentions using the Structural Equation Modelling (SEM) techniques. The chapters explain the interactions between personal (attitudes toward entrepreneurship and self-efficacy) and environmental (social and family norms and education) factors, and investigate how these factors affect students’ entrepreneurial career choice.